Toward sustainable food system: the role of livestock farming in Matiyani village in the Vhembe Biosphere Reserve, South Africa - Kone, Mukona T.; Budeli, Andani E.; Ramaano, Rerani (Frontiers in Sustainable Food Systems, 2025)
This study explored the role of livestock farming in Matiyani village toward achieving a sustainable food system, in the Vhembe Biosphere Reserve, South Africa. Africa has made advancements in addressing agriculture and rural development. Most rural communities in South Africa mainly rely on agriculture. At the same time, population growth and concerns about food security cannot be ignored. Therefore, agriculture presents itself as an important factor in the economy, relied upon by large populations. However, much focus seems to be placed on crop farming, with limited attention to livestock farming, particularly in indigenous communities. In cases where livestock farming is considered, it is usually from a large commercial scale, while ignoring the contribution of livestock farming in enhancing sustainable food systems. These livestock farming activities usually reflect the culture and economies of local communities. The study adopted a qualitative research design, with a sample of 29 livestock farmers from the Matiyani village. Livestock farmers in Matiyani village under the Hlanganani Livestock Forum in the Vhembe Biosphere Reserve, South Africa, through purposively sampled. Thematic analysis was employed for qualitative data through focus group discussions and a desktop study. This study explored the influence of livestock farming practices within the community that contribute to sustainable food systems. The outcomes of this study reveal how livestock farming is important for the sustainable food system of Indigenous communities by sustaining their livelihood through the sales of the livestock among themselves and within the commercial market. The study also found that livestock farming in this community does not only benefits economic activities but also provides social and environmental benefits, as livestock are used for community rituals and their manure as crop fertilizer. Furthermore, the study findings indicate that communities residing adjacent to protected areas face more challenges of human wildlife conflict, which, in most cases, they never receive compensation for the loss of their livestock caused by wildlife from these protected areas, which influences their lack of participation in sustainable food systems.